2012
DOI: 10.1016/j.euromechflu.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Design study of a regenerative pump using one-dimensional and three-dimensional numerical techniques

Abstract: Regenerative pumps are low cost, compact, able to deliver high heads at low flow rates. Furthermore with stable performance characteristics they can operate with very small NPSH. The complexity of the flow field is a serious challenge for any kind of mathematical modelling. This paper compares an analytical and numerical technique of resolving the performance for a new regenerative pump design. The performance characteristics computed by a CFD approach and a new one-dimensional model are compared and matched t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 7 publications
0
26
0
1
Order By: Relevance
“…In a more recent study, Deglon and Meyer [9] dem onstrated that the MRF technique and the standard k-s turbulence model could be efficiently used in CFD simulations of stirred tanks. The MRF technique was also successfully applied in CFD simulations of regenerative and centrifugal pumps [10,11], The location of the interface between the two frames of reference is important in order to minimize numerical errors associated with approximations at the interface. This topic was addressed by Zadravec et al [12], who found that as the size of the rotating fluid domain increases, the influence of numerical errors due to interpolation inaccuracies is reduced, hence resulting in more accurate results.…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…In a more recent study, Deglon and Meyer [9] dem onstrated that the MRF technique and the standard k-s turbulence model could be efficiently used in CFD simulations of stirred tanks. The MRF technique was also successfully applied in CFD simulations of regenerative and centrifugal pumps [10,11], The location of the interface between the two frames of reference is important in order to minimize numerical errors associated with approximations at the interface. This topic was addressed by Zadravec et al [12], who found that as the size of the rotating fluid domain increases, the influence of numerical errors due to interpolation inaccuracies is reduced, hence resulting in more accurate results.…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…However like all methods, it has its weaknesses. Often the geometry to be modelled has to be simplified due to limitations in processing capabilities, such as applying a coarse mesh in regions of detail, which may lead to inaccuracies [6]. There are two main theoretical models for describing the flow in regenerative pumps, each relying on a set of basic assumptions.…”
Section: Historymentioning
confidence: 99%
“…The increase in head is achieved through a momentum exchange between the impeller and the pumped fluid [3]. However, in contrast to the centrifugal pump, the pressure rise occurs in the peripheral rather than in the radial direction [5][6]. Perhaps what really distinguishes the RLR pump is its ability to develop high heads at relatively low flow rates in only one impeller stage [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Quil et al used a commercial code to investigate the fluid flow in a regenerative pump. They also carried out a new method of manufacturing to evaluate the influence of change in blade geometry on the efficiency of regenerative pump [11,12]. An experimental study was accomplished by Choi et al to investigate the effect of the impeller blade angle and its shape on regenerative pump performance.…”
Section: Introductionmentioning
confidence: 99%